Galactin-3 and brain natriuretic peptide versus conventional echocardiography in the early detection of cirrhotic cardiomyopathy - Wael A. Abbas,; Soheir M. Kasem Ahmed,; Amal M. Abdel Aal,; Amal A. Mahmoud,; Mohamed O. Abdelmalek,; Mohamed A. Mekky,; Mohamed A. A. Abozaid,; Ahmed K. Ibrahim, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Cirrhotic cardiomyopathy (CCM) is defined as an abnormal heart structure and function in cirrhotic patients. CCM includes systolic and diastolic dysfunction, electrophysiological abnormalities, and structural changes, both microscopic and macroscopic. Currently, there is no one diagnostic test that can identify patients with CCM. Evaluation of the validity of galactin-3 and brain natriuretic peptide (BNP) as biomarkers in the early detection of CCM in comparison to conventional echocardiography. Materials and Methods: A case control study was carried out in the Departments of internal medicine and tropical Medicine, Assuit University, Egypt. Seventy-one subjects were divided into the following three groups: 26 cirrhotic patients without ascites, 25 cirrhotic patients with ascites, and 20 healthy controls. All groups underwent clinical examination, and laboratory investigation including BNP, galactin-3, and echocardiography. Results: There was a significant difference between the three groups (p<0.001) with regard to corrected QT (cQT), BNP and galactin-3. Left ventricular diastolic dysfunction with different grades was the most recorded cardiac abnormality in the patient group I and II (88.5% and 96%; respectively) with significantly increased frequency and severity in ascetic patients and with the advancement of liver cirrhosis. BNP and galactin-3 were sensitive and specific biomarkers for the detection of diastolic dysfunction in cirrhotic patients (77.6%, 95.5%, 89.9% and 86.4%; respectively). Conclusion: Diastolic dysfunction is a common cardiac abnormality in cirrhotic patients that worsens with the advancement of cirrhosis. BNP and galactin-3 had higher sensitivity and specificity in the early detection of CCM compared with those of conventional echocardiography.